The Effect of Training and Employee Motivation on Employee Performance and Mediation by Employee Engagement at Muslimah Fashion Umkm - Ninda Aglina Ulfah; B. Medina Nilasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the effect of training and employee motivation on employee performance with employee engagement which is thought to be able to mediate training and employee motivation on employee performance. This study uses a quantitative method with the use of primary data sourced from questionnaires distributed to MSME employees in the Muslimah Fashion Sector in Jakarta. The research sample was selected using the proportionate stratified random sampling technique in order to obtain 146 respondents as the sample. The data analysis used to test the hypothesis is the structural equation model with